Establishing Employee Commitment: Respect or Pay? - Iqbal, Aimon; Munawar, Nousheen; Ali, Imran; Fatima, Nousheen (Journal of Management Studies and Development, 2024)
This research delves into whether employees prioritize workplace respect or Pay Satisfaction for their commitment to an organization, focusing specifically on the service sector, notably the banking industry. The overarching goal is to discern the determinants influencing employees' decisions to remain loyal to their current position or explore alternative job opportunities. Employing a cross-sectional, causal, and quantitative approach, primary data was collected through a structured and close-ended questionnaire targeting banking sector staff. The study revealed that employees exhibit divergent preferences, with some valuing respect at the workplace more than others. While pay satisfaction was identified as a correlated factor in employee commitment, the emphasis on workplace respect was notably higher. The research employed regression analysis to dissect the nuances of these preferences within different employee groups, shedding light on the varying intensities associated with each choice.